Investigations into the taxonomy of cultivars of Brassica campestris L. var. rapifera Metzg. Sinsk - McGuire, Frank E. (The University of Edinburgh, 1971)
With the advent of the Plant Variety Rights and Seeds Act of 1964, and with a view to the expected introduction of protection of certain Brassica species in the 1970's, an attempt has been made to deduce the high degree of synonymity which exists at present in turnip cultivars in the United Kingdom. A comprehensive collection of turnip cultivars being offered for sale on the British market in 1967 was obtained and by using established taxonomic characters together with suggested new criteria of 'bulb' shape and 'bulb’ measurements, a detailed classification of the cultivars has been evolved. Previously turnip cultivars could be divided into 13 main groups based on leaf type and bulb colour. These 13 major groups can now be further sub-divided into another 7, making a total of 20, by using the new taxonomic characters of bulb shape and bulb measurement. Cultivars previously classed as synonyms can now be identified as distinct
Keywords: Annexe MSc Digitisation Project 2022 Block 33; Turnip; Cultivars; Synonymity; Taxonomy; Classification